Feasibility Study on Pinela Yarn (Philippine Tropical Fabric) - Barretto, Ronilon M.; Reyes, Olaf Aaron C.; Taningco, Tristan Jan E.; Villanueva, Earl A. (College of Engineering, 1997)
Philippine Tropical Fabric Yarn, or Pinela Yarn, is a new Filipino made textile product developed by the Philippine Textile Research Association. It is unique in its use of abaca, banana, and pineapple fibers which are blended with cotton. Pinela Yarn is 100% bio-degradable, makes use of only natural fiber, and has no chemicals that are harmful to man and the environment. This study demonstrates the feasibility of the commercial production by a private enterprise of Pinela Yarn. In the study, it is shown that there is a market for Pinela Yarn. Pinela Yarn is sold primarily to local weavers. The manufacture of Pinela Yarn will help close the current and projected demand-supply gap of yarn by 0.33% to 0.40% of the total demand. Due to raw material constraints, a constant level of production of 960,000 kilograms of Philippine Tropical Fabric Yarn, is scheduled for the next five years. In order to sell this product, a marketing and sales plan is formulated. Annual selling expense, consisting of advertising and promotions, salaries of the marketing department, and other selling expenses, total P1.119.500. This output is limited by the size of the enterprise desired (a medium sized venture), and the supply base of raw materials used in the manufacture of the yarn. For the manufacture of Pinela Yarn, the production processes and the necessary equipment, tooling, and raw materials involved are developed. This would entail an aggregate plan of three seven hour shifts at 250 working days a year. A total project cost of P225,464,806.56 would be incurred. Suppliers for these are selected based on a set of criteria. The necessary facility for production is designed taking into account the space requirements, and the relationships and travel between different sections. The plant site is selected to be at Mayapa, Calamba, Laguna. The technical feasibility of the production of Pinela Yarn is demonstrated in the study. This project is financially feasible because it has a positive net present value of P38,801,730.20, its internal rate of return of 31.05% is nearly double the minimum attractive rate of return of 18%, funding from financial institutions can be obtained, it is capable of paying debts incurred, and it has a satisfactory output. The venture would be able to recover its investment in three years. This based on computations covering the next five years. The Project would generate a net income ranging from 20 to 58 million pesos for the first five years of operation. The enterprise to produce this Yarn is structured as a corporation, in consideration to the amount of financing required, with different departments differentiated by function. An organizational structure is developed in the study. The total manpower required for the various sections of this enterprise is given in the study. A total number of 109 employees will be needed. The project is not only a profit oriented enterprise, it also benefits society. The benefits are felt by the market/public, the local community, the national economy, and even the environment. One primary benefit concerns the "rule of origin" imposed by the United States of America on incoming trade goods. In order for Filipino exporters of finished textiles products to make use of subsidies and quotas granted to Philippine products, the yarn used by their products has to be locally. Pinela Yarn helps fill this urgent need, especially considering that locally produced yarn is relatively scarce. Additionally, this Project translates to jobs, growth of related industries, government profit from taxes and other fees, and an alternative environment-friendly product. Indeed Pinela Yarn is a feasible venture.